2016
DOI: 10.1123/jsep.2015-0145
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High- and Low-Anxiety Training on the Anticipation Judgments of Elite Performers

Abstract: 26We examined the effects of high-versus low-anxiety conditions during video-based 27 training of anticipation judgements by international-level badminton players facing serves and 28 the transfer to high-anxiety and field-based conditions. Players were assigned to a high-anxiety 29 training (HA), low-anxiety training (LA) or control group (CON) in a pre-training-post-test 30 design. In the pre-and post-test, players anticipated serves either from video under high-and 31 low anxiety conditions or live on-court… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 6 publications
0
32
1
1
Order By: Relevance
“…High-level sport is characterised by dynamic, uncertain and ever-changing interactions that place severe temporal demands upon athletes (Williams & Ericsson, 2005). Therefore the ability to anticipate the actions of opponents is essential (Alder et al, 2016). Superior anticipatory judgements are underpinned by efficient visual search behaviour (Mann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…High-level sport is characterised by dynamic, uncertain and ever-changing interactions that place severe temporal demands upon athletes (Williams & Ericsson, 2005). Therefore the ability to anticipate the actions of opponents is essential (Alder et al, 2016). Superior anticipatory judgements are underpinned by efficient visual search behaviour (Mann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In badminton, Alder et al (2014) found that international players utilised a visual search behaviour strategy consisting of fewer fixations of a longer duration compared to their less skilled counterparts. Moreover, the international players fixated on the kinematic locations of their opponent that were most salient for the upcoming shot type and direction (see also , Alder et al, 2016). If efficient visual search behaviours underpin effective anticipation, then threats to the efficiency of visual search behaviour may influence a player's ability to effectively anticipate their opponent's action.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Visual gaze has been used as an index of attention during performance on a specific task (e.g., anticipation), but thus far, only in a few published reports have gaze behaviours been recorded before and after an intervention or practice phase (for exceptions, see Alder, Ford, Causer, & Williams, 2016;Breslin, Hodges, Williams, Kramer, & Curren, 2007;Causer, Holmes, & Williams, 2011). Measures of gaze can help establish whether more stable or efficient patterns of visual search behaviour in some learners (i.e., longer duration fixations on information rich areas of a display) inform what information is being acquired, how improvements in performance are attained, and/or explain "learning" in the absence of performance effects.…”
Section: 2mentioning
confidence: 99%